الخطاب الصهيوني – السياسي والإعلامي – ودوره في تضخيم الخطر الوجودي للكيان الإسرائيلي - برهم, بنان عبد اللطيف (Al-Qurtas, 2026)
الخطاب الصهيوني – السياسي والإعلامي – ودوره في تضخيم الخطر الوجودي للكيان الإسرائيلي